2021
DOI: 10.47307/gmc.2021.129.s2.17
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 and hepatitis B Ambassador of Surabaya, Indonesia: Motivation, commitment, and knowledge of youth generation towards health programs in the pandemic era

Abstract: Background: To curb Corona Virus Diseases 2019 (COVID-19) pandemic and Hepatitis B further spread, the local Health Ministry collaborated with local communities to build COVID-19 and Hepatitis B Ambassador. This program utilizes the youth generation to support health promotion and health prevention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…The study found that there was a significant correlation between the participants' commitments to the degree of knowledge reflecting that commitment is an essential factor to increase the knowledge of youths regarding COVID-19. Knowing the motivation, commitment, and knowledge of the young generation might be an important step to gain the support of youths in health promotion programs [22].…”
Section: Discussionmentioning
confidence: 99%
“…The study found that there was a significant correlation between the participants' commitments to the degree of knowledge reflecting that commitment is an essential factor to increase the knowledge of youths regarding COVID-19. Knowing the motivation, commitment, and knowledge of the young generation might be an important step to gain the support of youths in health promotion programs [22].…”
Section: Discussionmentioning
confidence: 99%
“…One of which is a nursing student, and health students is one of the prospective medical workers who will later serve as the vanguard in handling COVID-19. It is crucial to determine these students' level of knowledge and perceptions of competence, considering the potential of graduate internships and then invited to the field because of uncertainty about how the pandemic will happen (11,12). In particular, Universities are asked to establish a panic-related management approach to encourage positive health behaviour among students (13).…”
Section: Introductionmentioning
confidence: 99%